PENGARUH KARAKTERISTIK ORIENTASI TEKNOLOGI TERHADAP KUALITAS PRODUK DAN PERBEDAAN KUALITAS PRODUK PERUSAHAAN CONSUMER GOODS DI SURABAYA - Wahyudiono Wahyudiono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
The aim of the study is to examine the effect of technology Orientation characteristics (commitment R & D, technology acquisition and technology application) and dummy variable to product quality  of Consumer Goods Companies in Surabaya. The population of the study is all Consumer goods (food and beverage companies), which are operated until the end of 2010, and located in Surabaya Industrial Estate Rungkut (SIER), the companies also joined in GAPMMI of East Java branch and received facilities from East Java Board of Investment. This research employs complete enumeration since the number of  population is relatively small (29 food and beverage companies), where as the analysis tool is multiple linier regression analysis with independent variable which are quantitative and qualitative (dummy variable). Multiple linier regression is used to analyse the effect of technology orientation characteristics that reflect three factors on product quality. Dummy variable is used to analyse the differences of product quality of Consumer Goods campanies with go public status and without go public status. The test results shows either simultaneously or parsial,  indicates that the variable of technology Orientation characteristics consisting of commitment R & D, technology acquisition and technology application have a  significant effect on product quality of Consumer Goods companies. And the result also show that product quality of consumer goods companies with go public status is higher than product quality of the consumer goods companies without go public status.